2015
DOI: 10.1007/s10508-015-0560-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neurophysiological Activation Patterns During Phonological Input Processing: An Influencing Factor for Normative Data

Abstract: In the context of neurophysiological normative data, it has been established that aging has a significant impact on neurophysiological correlates of auditory phonological input processes, such as phoneme discrimination (PD) and word recognition (WR). Besides age, sex is another demographic factor that influences several language processes. We aimed to disentangle whether sex has a similar effect on PD and WR. Event-related potentials (ERPs) were recorded in 20 men and 24 women. During PD, three phonemic contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 82 publications
0
5
0
1
Order By: Relevance
“…Some studies 27 32 33 demonstrated neurophysiological differences between gender, particularly for verbal abilities in favor of women. Research 27 32 33 indicates that, in general, the amplitude of MMN is greater in women than in men, whereas the latency is greater in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies 27 32 33 demonstrated neurophysiological differences between gender, particularly for verbal abilities in favor of women. Research 27 32 33 indicates that, in general, the amplitude of MMN is greater in women than in men, whereas the latency is greater in men.…”
Section: Discussionmentioning
confidence: 99%
“…Research 27 32 33 indicates that, in general, the amplitude of MMN is greater in women than in men, whereas the latency is greater in men. Nevertheless, these differences occur only for stimuli with phonemics contrasts.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The study points to amplitude of MMN tending to be higher among females in relation to males when verbal stimuli are used; however, this does not occur with latency, which presents higher values for males. 31 The authors believe that higher amplitudes among females may be related to a higher bundling of enveloped neurons, as well as to the better synchrony of the neural network. Nevertheless, such findings were not evidenced in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the P200 has been reported to be consistently associated with greater arousal levels (Carretié et al, 2001; Schutter, de Haan, & van Honk, 2004) and attention capturing by target stimuli (Potts, 2004; Potts, Martin, Burton, & Montague, 2006), supporting the idea that neural processes supporting attention facilitation to salient stimuli may be represented by the P200 (see (Kotz & Paulmann, 2011) for a review). Interestingly, along with several behavioral and ERP studies reporting sex differences in attention allocation during processing of emotional stimuli in adults (Kraines, Kelberer, & Wells, 2017; Pfabigan, Lamplmayr-Kragl, Pintzinger, Sailer, & Tran, 2014; Stoet, 2017; van Hooff, Crawford, & van Vugt, 2011), emerging evidence indicates sex differences in the P200 ERP components during several cognitive processes (e.g., (Aerts, van Mierlo, Hartsuiker, Santens, & De Letter, 2015), with males having a larger fronto-central P200 peak amplitude and a shorter P200 latency period compared to females (Bourisly & Shuaib, 2018).…”
Section: Introductionmentioning
confidence: 93%